Smoking and endometriosis: A narrative review - Alexandre Vallée; Anis Feki; Loic Josseran; Jean-Marc Ayoubi (Tobacco Induced Diseases)
Endometriosis is a chronic gynecological disorder affecting 6–10% of women of reproductive age. While its etiology is multifactorial, growing evidence suggests that tobacco smoking may contribute to its development and progression through inflammatory, oxidative, and hormonal mechanisms. This narrative review examines the relationship between tobacco smoking and endometriosis, integrating molecular insights to clarify potential biological pathways and highlight areas for future research. A search was conducted in PubMed/MEDLINE and Web of Science, including only original research articles published in English. Studies on both human and animal models were considered, without restrictions on participant age, to provide a comprehensive overview of tobacco-related mechanisms in endometriosis. Tobacco smoke components, such as nicotine and polycyclic aromatic hydrocarbons, can initiate and sustain an inflammatory response, leading to the release of pro-inflammatory cytokines and recruitment of immune cells. Tobacco smoking also induces oxidative stress, disrupting cellular functions and damaging DNA. Moreover, it can cause hormonal dysregulation and interfere with hormonerelated signaling pathways. Epigenetic modifications, including DNA methylation and histone modifications, can also be induced by tobacco smoking. These changes affect the expression of genes involved in inflammation, cell proliferation, and hormone signaling, contributing to the pathogenesis of endometriosis. Future research should prioritize longitudinal studies with objective biomarkers to strengthen causal inference. Studies integrating omics approaches can further clarify tobacco-induced molecular alterations in endometriosis. Public health policies should incorporate targeted smoking prevention and cessation programs for women at risk.